Implementasi Protokol AMQP pada Sistem Monitoring Debit Air Depot Air Minum Isi Ulang - Ridwan Eko Prasetyo; Heru Nurwarsito (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The increasing demand for drinking water is corresponding to the increasing amount of refill drinking water depot industry. However, the refill drinking water depot industry currently still manually records their water sales. Sales recording can be seen the parameter of the amount of water discharge. The amount of water discharge can be found by making a monitoring system. The monitoring system can be built with Internet of Things (IoT) technology. In the application of IoT, a communication protocol between entities is needed to exchange data. In this study, AMQP protocol was used. AMQP is a reliable messaging protocol with acknowledgment as a guaranteed messaging feature. The implementation of AMQP protocol is divided into three parts; producer, broker, and consumer. Producer acts as component that sends data. Consumer acts as component that receives data. Broker acts as communication intermediary between producer and consumer. In this study, producer is implemented using raspberry pi device. The implementation of the broker uses AMQP cloud service, while the consumer is implemented on client's laptop. From the results of the conducted performance test, the results obtained are with packet loss parameter of 0% and delay parameter of 63.06 ms, which are in the very good category of the test parameter. As well as the jitter parameter of 0.32 ms which is included in the good parameter category.